Phase‐Separated Liposomes Hijack Endogenous Lipoprotein Transport and Metabolism Pathways to Target Subsets of Endothelial Cells In Vivo. Issue 10 (19th January 2023) - Arias‐Alpizar, Gabriela; Papadopoulou, Panagiota; Rios, Xabier; Pulagam, Krishna Reddy; Moradi, Mohammad‐Amin; Pattipeiluhu, Roy; Bussmann, Jeroen; Sommerdijk, Nico; Llop, Jordi; Kros, Alexander; Campbell, Frederick
Abstract: Plasma lipid transport and metabolism are essential to ensure correct cellular function throughout the body. Dynamically regulated in time and space, the well‐characterized mechanisms underpinning plasma lipid transport and metabolism offers an enticing, but as yet underexplored, rationale to design synthetic lipid nanoparticles with inherent cell/tissue selectivity. Herein, a systemically administered liposome formulation, composed of just two lipids, that is capable of hijacking a triglyceride lipase‐mediated lipid transport pathway resulting in liposome recognition and uptake within specific endothelial cell subsets is described. In the absence of targeting ligands, liposome‐lipase interactions are mediated by a unique, phase‐separated ("parachute") liposome morphology. Within the embryonic zebrafish, selective liposome accumulation is observed at the developing blood‐brain barrier. In mice, extensive liposome accumulation within the liver and spleen – which is reduced, but not eliminated, following small molecule lipase inhibition – supports a role for endothelial lipase but highlights these liposomes are also subject to significant "off‐target" by reticuloendothelial system organs. Overall, these compositionally simplistic liposomes offer new insights into the discovery and design of lipid‐based nanoparticles that can exploit endogenous lipid transport and metabolism pathways to achieve cell selective targeting in vivo. Abstract : In this study, a liposome formulation, composed of just two lipids and characterized by phase separation, is described. In vivo, after systemic administration in zebrafish and mice, this formulation is capable of hijacking a triglyceride lipase‐mediated lipid transport pathway resulting in liposome recognition and uptake within specific endothelial cell subsets.